Defining Worn Out Workwear: Exploring how to assess garments for reuse within a laundry system - Hall, Cathryn Anneka; Taudal, Sarafina Liv; Bundgaard-Nielsen, Mette Julie (Proceedings of the 6th Product Lifetimes and the Environment Conference (PLATE2025), 2025)
This paper explores how to create an objective assessment criterion for ‘worn out’ workwear within an industrial laundry system. Undertaken during the ReSuit project, the research used Elis (laundry service provider) as a case study. Four styles of light workwear (2x t-shirts and 2x trousers) were selected because they represented the products with highest numbers of discards. During a field study, the researchers visually analysed a week’s worth of these discarded garments for a variety of types of wear and tear. The research found that wear and tear could be categorised across four themes: holes, stains, pilling and colour. A traffic light system was created in which garments were assessed as Green: Reusable. Yellow: Normal wear and tear with the potential for reuse. Red: Worn out (discard for recycling). From this assessment guides were created, both digital (to be printed) and physical (exemplars). Working within the limitations of the research, these guides did not provide definitive definitions of worn-out workwear, rather were to ‘start the conversation’ of where the line is drawn between reuse and discard within the workwear sector. This research concludes that there is a huge potential for the workwear sector to reuse clothing and extend the lives of the products and further research should seek to streamline and test this worn out workwear assessment criteria.